Does the Thalamo-Cortical Synchrony Play a Role in Seizure Termination? - Evangelista, Elisa; Bénar, Christian; Bonini, Francesca; Carron, Romain; Colombet, Bruno; Régis, Jean; Bartolomei, Fabrice (Frontiers in Neurology, 2015)
The mechanisms underlying seizure termination are still unclear despite their therapeutic importance. We studied thalamo-cortical connectivity and synchrony in human mesial temporal lobe seizures in order to analyze their role in seizure termination. Twenty-two seizures from ten patients with drug-resistant mesial temporal lobe epilepsy undergoing pre-surgical evaluation were analyzed using intracerebral recordings (stereoelectroencephalography, SEEG). We performed a measure of SEEG signal interdependencies (non-linear correlation), to estimate the functional connectivity between thalamus and cortical regions. Then we derived synchronization indices, namely global, thalamic, mesio-temporal and thalamo-mesio temporal index at the onset and the end of seizures. In addition, an estimation of thalamic “outputs and inputs” connectivity was proposed. Thalamus was consistently involved in the last phase of all analyzed seizures and thalamic synchronization index was significantly more elevated at the end of seizure than at the onset. The global synchronization index at the end of seizure negatively correlated with seizure duration (p= 0.045) and in the same way the thalamic synchronization index showed an inverse tendency with seizure duration. Six seizures out of twenty-two displayed a particular thalamo-cortical spike and wave pattern (SWP) at the end. They were associated to higher values of all synchronization indices and outputs from thalamus ( p = 0.0079). SWP seizures displayed a higher and sustained increase of cortical and thalamo-cortical synchronization with a stronger participation of thalamic outputs. We suggest that thalamo-cortical oscillations might contribute to seizure termination via modulation of cortical synchronization. In the subgroup of SWP seizures thalamus may exert a control on temporal lobe structures by inducing a stable hypersynchronization that ultimately leads to seizure termination.